Topologically protected optical pulling force on synthetic particles through photonic nanojet - Ren Yu-Xuan; Frueh Johannes; Zhang Zhisen; Rutkowski Sven; Zhou Yi; Mao Huade; Kong Cihang; Tverdokhlebov Sergei I.; Liu Wen; Wong Kenneth K. Y.; Li Bo (Nanophotonics)
A dielectric microsphere concentrates light into a photonic nanojet (PNJ), and swims towards the near-infrared laser in response to the nanojet-mediated force. In contrast, a Janus particle with an opaque metal layer was thought to be impossible to concentrate light into a stable nanojet. However, the Janus particle may experience optical torque owing to the inhomogeneous composition on both sides even in linearly polarized non-resonant light. Herein, we report on topologically protected PNJ produced by a synthetic Janus particle, and observed the backaction force on the Janus particle. Due to symmetry, the counter-propagating beams can both form PNJ on the respective opposite sides, and pull Janus particles towards respective sources. Furthermore, we unveil that the hysteresis on backaction force with respect to the injection power also exists on synthetic Janus particle compared with their dielectric counterparts. Additionally, the magnitude of the backaction force varies between power increase and decrease stages even with the same laser power. We anticipate that the observation offers great possibilities to pull irregular particles by concentrating light with the particle, and such scheme may be applied for parallel particle manipulation and classification.